Pengelolaan Media Sosial @toucheid Dalam Meningkatkan Brand Awareness - Ardianti, Raissa Khalilah; Anisa, Renata (Marcommers : Jurnal Marketing Communication and Advertising, 2024)
In forming brand awareness, a special role is required to create a positive image of the company in public. Social media has become one of the important things for a public relations professional to execute their programs. The aim of this research is to understand the processes of sharing, optimizing, managing, and engaging on the @toucheid account in enhancing brand awareness. The research method used is a descriptive method with a qualitative technique. Data collection techniques include observation, interviews, and literature review. In social media management, there is a model called The Circular Model of SoMe by Regina Luttrell. The research findings demonstrate how Touche Development Center forms brand awareness among the public through social media management. Touche Development Center has not yet effectively implemented the Manage and Optimize stages. However, they have maximized their performance in the Share and Engage stages. Touche Development Center has correctly chosen Instagram as their primary platform to connect with the public with the aim of increasing brand awareness. However, in the Engage stage, Touche Development Center needs to optimize their performance in engaging with influencers to enhance engagement on the @toucheid Instagram account.